ALK-positive Large B-Cell Lymphoma Presenting as a Circumscribed Breast Mass with Germinal Center Immunophenotype. (April 2023) - Yan, Mingfei; Khattab, Ruba; Meyerson, Howard
We report a rare case of ALK-positive large B cell lymphoma which initially presented as a circumscribed breast mass in a young woman mimicking fibroadenoma. The lymphoma demonstrated typical immunoblastic morphology with monomorphic round nuclei and prominent central nucleoli. Immunophenotypically, the lymphoma was positive for MUM1, CD138, BOB1, OCT2, PAX5 (focal), CD4, and was negative for CD20, CD79a and all other T cell antigens. Immunostaining for the ALK protein revealed the characteristic granular cytoplasmic staining typical for ALK-positive large B cell lymphoma with an ALK::CTCL fusion confirmed on genomic profiling study. Notably the cells also expressed CD10 and BCL6. Staging revealed disseminated disease with blood, bone marrow and liver involvement. To our knowledge, this is the first report of ALK-positive large B cell lymphoma initially presenting as a breast lesion. Additionally, expression of CD10 and BCL6 suggested a germinal center origin for the lesion.